Impact of Rice Bran Adulteration with Rice Husk on the Performance, Digestibility, and Organs of Garut Rams in Corn Straw Silage-Based Rations - Rosani, Urip; Hernaman, Iman; Hidayat, Rahmat; Hidayat, Darmawan; Pazla, Roni; Begna, Regasa (Jurnal Ilmu-Ilmu Peternakan, 2026)
This research was conducted to determine the effect of rice husk in a corn straw silage-based ration on the performance of Garut sheep. In this study, a completely randomized design (CRD) was used to determine the effects of rice husk on performance, digestibility, and organs. In this study, different amounts of rice husk were added to a corn straw silage-based diet, and each treatment was repeated five times. Twenty-five five-month-old male Garut sheep weighing 17.13±1.65 kg were divided into 5 groups, with one sheep per repetition. Each group was given an experimental diet consisting of the following: RH0 = 60% corn straw silage + 40% rice bran + 0% rice husk, RH1 = 60% corn straw silage + 30% rice bran + 10% rice husk, RH2 = 60% corn straw silage + 20% rice bran + 20% rice husk, RH3 = 60% corn straw silage + 10% rice bran + 30% rice husk, and RH4 = 60% corn straw silage + 0% rice bran + 40% rice husk. These findings indicated that higher levels of rice husk in the diet reduced performance, body weight, and weight gain and increased the weight of the digestive tract. Overall, the addition of rice husk in this study decreased the performance